2023
DOI: 10.3390/molecules28052386
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Molecules Derived from Plants in Managing Dengue Vector Aedes aegypti (Linn.)

Abstract: Mosquitoes are the potential vectors of several viral diseases such as filariasis, malaria, dengue, yellow fever, Zika fever and encephalitis in humans as well as other species. Dengue, the most common mosquito-borne disease in humans caused by the dengue virus is transmitted by the vector Ae. aegypti. Fever, chills, nausea and neurological disorders are the frequent symptoms of Zika and dengue. Thanks to various anthropogenic activities such as deforestation, industrialized farming and poor drainage facilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…Some reports indicated that the use of NMRPs might be the main reason. 11,12 However, to the best of our knowledge, there is no study comprehensively recognizing toxic components and evaluating relative adverse consequences of NMRPs to date.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports indicated that the use of NMRPs might be the main reason. 11,12 However, to the best of our knowledge, there is no study comprehensively recognizing toxic components and evaluating relative adverse consequences of NMRPs to date.…”
Section: ■ Introductionmentioning
confidence: 99%
“…At the same time, however, dizziness, nausea, abdominal pain, and other safety incidents begin to be reported when children use NMRPs. Some reports indicated that the use of NMRPs might be the main reason. , However, to the best of our knowledge, there is no study comprehensively recognizing toxic components and evaluating relative adverse consequences of NMRPs to date.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups of phytochemicals such as alkaloids, steroids, terpenoids, essential oils and phenolics from different plants have been reported previously for their insecticidal activities (Ghosh et al 2012). Development of plant-based insecticides and repellents has been focused by many recent studies (Maia & Moore 2011;Şengül Demirak & Canpolat 2022;Deng et al 2023;Priya et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…While being effective, the phytochemicals reduce the risk of potentially adverse ecological effects. Also, they may prevent the possibility of the resistance that synthetic chemical insecticides typically bring about after prolonged use (Monzon et al 1994;Priya et al 2023). Unlike conventional insecticides which are based on a single active ingredient, plant derived insecticides comprise botanical blends of chemical compounds which act concertedly on both behavioral and physiological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Mosquitoes are one of the main carriers of dangerous viruses that spread severe and fatal diseases worldwide (Edwin et al 2016;Priya et al 2023). Mosquitoes spread the greatest number of fatal diseases, including malaria, dengue, chikungunya, elephantiasis, and other arthropods (Priya et al 2023). Within the Culicidae family, Genus Aedes is known to pose a signi cant global public health threat.…”
Section: Introductionmentioning
confidence: 99%